An Exploratory Analysis of Violent Offending and the Acquired Capability for Suicide in Male Prisoners - Mandracchia, Jon (International journal of offender therapy and comparative criminology, 2018)
Recently, the Interpersonal Theory of Suicide has offered some understanding as to why inmates are at a disproportionately high risk to die by suicide. The present study was designed to investigate how one aspect of the theory, the acquired capability for suicide, may differ between prison inmates with violent offenses versus those without. Data from 343 male prisoners within the Mississippi Department of Corrections were used to examine potential differences between these two groups on scales of the Acquired Capability for Suicide Scale. Contrary to the hypothesis that violent offenders would evidence higher levels of acquired capability, only the Spectator Enjoyment of Violence subscale was significantly different between the two groups, with nonviolent offenders producing higher scores. Potential explanations for these findings and implications for correctional mental health care providers are discussed.